Tantangan dan Manfaat Pendekatan Bottom Up dalam Pembangunan Berkelanjutan di Kabupaten Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Sustainable development has become the main framework in global efforts to address the imbalance between economic growth, social justice, and environmental preservation. Amid global challenges such as climate change, rapid urbanization, and social inequality, the bottom-up approach has emerged as an alternative strategy that emphasizes the active participation of local communities in development planning and implementation. This study aims to identify and analyze the challenges and benefits of a bottom-up approach to sustainable development. The method used is a literature study, integrating the results of the review. The results of the study show that this approach brings significant benefits, namely increased social inclusion, encouragement of local innovation, and strengthening of environmental sustainability through community participation. These benefits are manifested in increased community ownership of programs, which encourages local adaptation initiatives, such as traditional irrigation techniques to reduce the impact of drought, as well as the implementation of organic farming programs and mangrove forest management. However, the implementation of the bottom-up approach in Kupang Regency faces substantial challenges, which are divided into resource constraints (including human and financial resources) and coordination issues. Resource constraints, such as lack of access to education and technology, can hamper program implementation.